Numerical characteristics of peer to peer (P2P) internet online hybrid test system and its application to seismic simulation of SRC structure. - Wang, Tao (Earthquake engineering & structural dynamics.)
The peer to peer (P2P) Internet online hybrid test system has been developed for the seismic simulation of a structure. In this study, the stability and accuracy of the system are investigated analytically by studying the spectral radius of the recursive matrix of the test scheme featuring a two round quasi Newton test scheme. The applicability of the system is further examined by exploring the seismic responses of a complex structure, a steel encased reinforced concrete (SRC) structure with a steel tower on the top. The structure is divided into two numerical substructures and one tested part for hybrid test. The numerical substructures are simulated by sophisticated finite element method (FEM) models with material nonlinearities to capture local plastifications. Two types of FEM programs, namely OpenSEES and ABAQUS, which are suitable for the SRC part and the steel tower, respectively, are employed. The results demonstrate that the P2P system is able to simulate complex structures with significant nonlinearities. As compared with the previous study in which two elastic numerical substructures were considered, increase in the number of iterations in this study is not significant, because the associated nonlinearities are limited due to the small time interval adopted in the test.